The Counseling Training Environment Scale: Initial Development and Validity of a Self-Report Measure to Assess the Counseling Training Environment. (2nd October 2019) - Lau, Jared M.; Ng, Kok-Mun; Vallett, David B.
Abstract: The Counseling Training Environment Scale (CTES) was developed as a self-report measure that assesses the training environment of counseling and related programs. The authors describe the multiphase mixed-methods design used to create and psychometrically evaluate the CTES and present findings that support initial validation and usability of the CTES.